2016
DOI: 10.1007/s11427-016-5003-z
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol: phytoalexin of cotton

Abstract: Sesquiterpenoids are a class of 15-carbon secondary metabolites that play diverse roles in plant adaptation to environment. Cotton plants accumulate a large amount of sesquiterpene aldehydes (including gossypol) as phytoalexins against pathogens and herbivores. They are stored in pigment glands of aerial organs and in epidermal layers of roots. Several enzymes of gossypol biosynthesis pathway have been characterized, including 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) and farnesyl diphosphate synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…Gossypol, the best ligand found so far, is a phytoalexin abundantly present in cotton, one of the main host plants of H. armigera (Rajapakse and Walter, 2007 ). Gossypol contents of 0.4–2% have been reported, depending on tissue and developmental stage (Cai et al, 2004 ; Tian et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gossypol, the best ligand found so far, is a phytoalexin abundantly present in cotton, one of the main host plants of H. armigera (Rajapakse and Walter, 2007 ). Gossypol contents of 0.4–2% have been reported, depending on tissue and developmental stage (Cai et al, 2004 ; Tian et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…conferring atropselectivity to the oxidative coupling of hemigossypol (Effenberger et al, 2015). This reaction constitutes the final step in the biosynthesis of the sesquiterpenoid dimer gossypol, an important natural product and defense compound in cotton plants (Wagner et al, 2012;Tian et al, 2016). These findings indicate that the role of DIRs is not restricted to lignan biosynthesis but extends to entirely different biosynthetic pathways in plant secondary metabolism.…”
mentioning
confidence: 90%
“…18 Gossypol and derivatives play important roles in defense against the pests and pathogens due to their cytotoxicity. 19 Studies in mammals, including humans, have shown that the members of the CYP1, CYP2, CYP3 and CYP4 subfamilies are involved in detoxification of xenobiotic compounds such as drugs, environmental pollutants, many natural products and ethanol. 2 This current research demonstrated that these four plant allelochemicals can regulate the expression of three newly identified members of the CYP6 subfamily.…”
Section: Discussionmentioning
confidence: 99%